Implementation of Strategy Concentration on the Sustainability of Non-Profit Organizations (Case Study: Syekh Yusuf Sungguminasa Hospital, Gowa Regency) - Risal Tudu (Journal of Entrepreneurship and Financial Technology, 2023)
Study This aim to find out how the implementation of strategic concentration on vertical growth and horizontal growth is seen from the customer's perspective on sustainability Syekh yusuf hospital really district Gowa . Qualitative methods are used in this study. The technique used in data collection is triangulation , that is do interview , observation and collection document . The data sources in this study consists from primary data and secondary data . Research results This show that syekh yusuf hospital was seen facet growth vertical , has a position strong competitive in competitive industry . Meanwhile , Syekh yusuf hospital in terms of growth horizontally at the center city Sungguminasa and is the only one House Sick Regional Public in Kab . Gowa which has a very strategic position . Then from the customer side, Syekh Yusuf general hospital pointed out amount complaints that arose the more decrease from year to year , which means party Hospital has an effort to fulfill need nor satisfaction patient .